Contamination of food with residues of antibiotics in the sulphonamide class, risk can be avoided - Carmen Lidia Chitescu; Anca Nicolau (Medicamentul Veterinar, 2010)
Sulfadimethoxine, sulfamethoxazole, sulfaquinoxaline and sulfadiazine are the most common usedsulfonamides in veterinary practice. The recommended withdrawal periods if not observed before slaughteringof the medicated animals, the products may obtain from such animals may be contaminated with residue. Theinterest in having reliable methods able to detect low amounts of sulfonamides in food is very actual. In thisstudy, a multiresidue analysis was performed to simultaneously determine those four sulfonamides in chickenmuscle tissue by the Waters LC.Criteria of validation: specificity, accuracy, precision, limit of detection, limit of quantification, and linearity,according to the European Commission Decision 2002/657/EC, show that the method can detect differentkinds of sulfonamides within one run, without mass spectrometry analyses, or Fluor metric derivatization ofanalyts.The method is accurate, simple, economical in both time and cost, capable of detecting sulfonamidesresidues below the maximum residue limits (MRL) and easy to perform to routine samples, in normal conditionof laboratory.The sulfonamides were extracted with acetonitrile and acetone and dichloromethane. N-hexane wasadded for defeating the sample. Separation was carried out on a Zorbax SB- C18 analytical column, using asmobile phase a mixture of 75:25 = di-natrium-hydrogenphosphat solution 6 g/1000 ml (pH = 8.5) : methanol.The detection wavelength was set at: 254 nm Calibration graphs were linear with very good correlationcoefficients in the concentration range from 0.320 to 1.5μg /mL. The limits of quantification (LOQ) for thesulfonamides were in the range of 6.6–0.34 μg /kg. The recovery for spiked chicken muscle with 50–150 μg/kg ranged more than 70%. The relative standard deviation (Reds) of the sulfonamides for six measurementsat 50 go/kg, 100 μg /kg and 150 μg /kg was less then 15%.The applicability of the method to the analysis of chicken muscle tissue was demonstrated.